"Work‐to‐Work" exercise slows pulmonary oxygen uptake kinetics, decreases critical power, and increases W' during supine cycling. Issue 21 (13th November 2018) - Goulding, Richie P.; Roche, Denise M.; Marwood, Simon
Abstract: We have previously demonstrated that the phase II time constant of pulmonary oxygen uptake kinetics ( τ v ˙ o 2 ) is an independent determinant of critical power (CP) when O2 availability is not limiting, that is, during upright cycle exercise in young, healthy individuals. Whether this causative relationship remains when O2 availability is impaired remains unknown. During supine exercise, which causes an O2 availability limitation during the exercise transition, we therefore determined the impact of a raised baseline work rate on τ v ˙ o 2 and CP. CP, τ v ˙ o 2, and muscle oxygenation status (the latter via near‐infrared spectroscopy) were determined via four severe‐intensity constant‐power exercise tests completed in two conditions: (1) with exercise initiated from an unloaded cycling baseline (U→S), and (2) with exercise initiated from a moderate‐intensity baseline work rate of 90% of the gas exchange threshold (M→S). In M→S, critical power was lower (U→S = 146 ± 39 W vs. M→S = 132 ± 33 W, P = 0.023) and τ v ˙ o 2 was greater (U→S = 45 ± 16 sec, vs. M→S = 69 ± 129 sec, P = 0.001) when compared to U→S. There was no difference in tissue oxyhemoglobin concentration ([HbO2 + MbO2 ]) at baseline or during exercise. The concomitant increase in τ v ˙ o 2 and reduction in CP during M→S compared to U→S shows for the first time that τ v ˙ o 2 is an independent determinant of CP in conditions where O2 availability is limiting. Abstract : We have previously shown that oxygen uptake kinetics are a determinant of critical power in the upright position, where oxygen availability is not limiting. The present data show that in the supine position, which causes an oxygen availability limitation, slowing oxygen uptake kinetics via work‐to‐work exercise resulted in a reduction in critical power. Hence, this study suggests that oxygen uptake kinetics are an important determinant of critical power, regardless of the sufficiency of oxygen availability.